HOPE DAN AL-RAJA' DALAM PERSPEKTIF PSIKOLOGI DAN TASAWUF - Ein, Indy Hurun (Jurnal Ilmiah Penelitian Psikologi, 2021)
This study aims to explore the concept of hope and al-raja' both in the psychological perspective tasawuf. This approach is also mainly discussed in the field of islamization of knowledge. This is a qualitative research and library research as its method. The similarities between hope and al-raja' are mental representation, vigorous desire, and goals regarding hope of both concepts. Then, the differences between those are acquisitions of knowledge, kinds of goal, and value of each concept